Pemberantasan Revenge Porn di Lingkungan Sekolah Menengah Atas Ditinjau dengan Hukum Positif di Indonesia - Fauzan, Muhammad; Fil'Awalin, Hanif; Aulyanti, Davina Dewi; Desthabu, Meurina; A, Biyandra Timothee; Zahra, Lintang Aulia; Situmeang, Zefanya Angelica; Welgaputri, Feby; Naufal, Muhammad; Siregar, Karina Josephine; Respati, Adnasohn Aqilla; Bakhtiar, Handar Subhandi (Jurnal Hukum Statuta, 2023)
Abstract Revenge Porn is booming among children or high school students who meet. More than that, there are rules for revenge porn itself in the laws and regulations. Therefore, there is a need for further research on revenge porn as a crime, the regulation of revenge porn is reviewed by Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 12 of 2022 concerning the Crime of Sexual Violence, and to know the reporting procedure when there is a porn revenge case. The research method used is normative research with an approach to laws and regulations. The data collection method used in this research is literature study. The results of this study indicate that revenge porn is a crime if there is an intention of the perpetrator to take revenge on the victim due to several factors such as the hurt experienced by the perpetrator. In addition, there can also be coercion and extortion that can aggravate the perpetrator when it is reported by the victim. In the ITE Law, there is a provision for revenge porn which is contained in Article 27 Paragraph (3). The relevance between the ITE Law and TPKS is the opening of electronic devices in the ITE Law that can be used for the needs of victims in reporting victim evidence with the TPKS Law. The procedure for reporting porn revenge cases can be seen in the Regulation of the Head of the Indonesian Police Number 6 of 2019 concerning Criminal Investigations.